Welfare costs of coordinated infrastructure investments: the case of competing transport modes. Issue 2 (4th May 2017) - Meade, Richard; Grimes, Arthur
ABSTRACT: Infrastructure investments such as in rail and road networks are often undertaken by different parties that have differing degrees of vertical integration into downstream rolling stock (i.e. train and truck) investments. We analyse the impacts on freight transport and welfare outcomes of different institutional approaches to investment coordination across multiple freight modes (rail and road) in the presence of upstream and downstream cost-reducing investments in each mode. We show that welfare is reduced when a profit-maximising transport infrastructure investor correctly anticipates the advent of a future competing infrastructure. This is because myopically failing to anticipate future competition results in welfare-enhancing over-investment. We further show that presciently anticipating inter-modal competition is not solely responsible for reduced welfare, with additional vertical and horizontal coordination issues also at work. Our model can be applied to a range of applications that deal with multiple competing infrastructure investments.